Sensibility, Melancholia, and Subjectivity in Mary Robinson’s Sappho and Phaon - Rosenova, Rayna (Romanticism on the Net)

(untitled) (Université de Montréal, 2018)
Mary Robinson’s sonnet sequence Sappho and Phaon: In a Series of Legitimate Sonnets (1796) is at once a celebration of the Greek poet’s eminence, as Robinson suggests in the preface, and a commentary on the reason and sensibility dialectic that dominated the 18th century. As such, it dramatizes the conflict between reason and sensibility, which is here also associated with erotic desire, showing the repercussions that the excess of feeling has upon the self without the governing principle of reason. This essay argues that Robinson drew upon the pathology of love melancholy, as well as on sublime and gothic aesthetics, to render the state of disjointed selfhood as a personal and artistic crisis which cannot be sublimated into art, and which subsequently results in the poet’s creative impasse and death. It also stresses the idea that through Sappho, Robinson aimed to represent the figure of the eighteenth-century woman writer, showing the need for a balance between reason and feeling so that desire could be transformed into artistic energy to serve a social purpose within the public sphere, addressing more universal issues of the human condition instead of focusing on private sorrows.